2005
DOI: 10.1074/jbc.m502540200
|View full text |Cite
|
Sign up to set email alerts
|

G-protein-coupled Receptor Signaling Components Localize in Both Sarcolemmal and Intracellular Caveolin-3-associated Microdomains in Adult Cardiac Myocytes

Abstract: This study tests the hypothesis that G-protein-coupled receptor (GPCR) signaling components involved in the regulation of adenylyl cyclase (AC) localize with caveolin (Cav), a protein marker for caveolae, in both cellsurface and intracellular membrane regions. Using sucrose density fractionation of adult cardiac myocytes, we detected Cav-3 in both buoyant membrane fractions (BF) and heavy/non-buoyant fractions (HF); ␤ 2 -adrenergic receptors (AR) in BF; and AC5/6, ␤ 1 -AR, M 4 -muscarinic acetylcholine recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
196
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(208 citation statements)
references
References 46 publications
10
196
2
Order By: Relevance
“…By use of the same non-detergent rafts preparation method employed in this study, we and others have found that mu, delta, or kappa opioid receptors are mainly associated with lipid rafts in several tissues/cells, including rat brain CPu, human placenta, rat cardiac myocytes, NG108-15 cells, HEK293 cells and CHO cells [13,17,20,27,28]. In this regard, the MOR in the rat thalamus is an exception.…”
Section: Thalamus: An Exception Regarding Opioid Receptors-lipid Raftmentioning
confidence: 58%
“…By use of the same non-detergent rafts preparation method employed in this study, we and others have found that mu, delta, or kappa opioid receptors are mainly associated with lipid rafts in several tissues/cells, including rat brain CPu, human placenta, rat cardiac myocytes, NG108-15 cells, HEK293 cells and CHO cells [13,17,20,27,28]. In this regard, the MOR in the rat thalamus is an exception.…”
Section: Thalamus: An Exception Regarding Opioid Receptors-lipid Raftmentioning
confidence: 58%
“…Relevant GPCRs and effector molecules also associate with cardiac caveolae/caveolin-3 (Head et al, 2005).…”
Section: Cell Membrane Localisation -Membrane Rafts Caveolae and Cavmentioning
confidence: 99%
“…Many 7-TMRs/GPCRs have been shown to locate in and regulated by lipid rafts (Pike, 2003;Chini and Parenti, 2004;Ostrom and Insel, 2004), including opioid receptors (Head et al, 2005;Xu et al, 2006;Zhao et al, 2006;Patel et al, 2006;Huang et al, 2007). For example, MOR expressed in HEK293 cells was found by Zhao et al (2006) to be mainly localized in lipid rafts domains of plasma membranes and this localization was required for MOR-mediated adenylyl cyclase superactivation.…”
Section: Introductionmentioning
confidence: 99%